Annual Plan, 1989-90 Orissa - Planning Commission (Planning Commission, 1988)
During the mid year of Seventh Plan, i.e. 1987-88, the economy experienced a severe jolt on account of drought. The decline in autumn and winter rice production alone was of the order of 13.6 lakh tonnes from that of 1986-87. The production of these crops touched a low level of 31 lakh tonnes. 259 out of 314 blocks of the State were severely affected by drought. Withdrawal of monsoon from the 3rd week of July and a continuous dry spell in August was responsible for serious crop damage in almost all parts of the State.
Government of Orissa, Planning and Co-ordination Department